Digital Transformation in MSME Human Resources Management: Adaptation Strategies Towards Sustainable Business - Akh.Fawaid; Asep Dana Saputra; Hery Suprayitno; Agus Hermawan; Puji Handayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Digital transformation in human resource management (HR) is a challenge as well as an opportunity for MSMEs in an effort to realize business sustainability. This research aims to explore how the digital adaptation process is carried out in MSME HR management practices, as well as identify the challenges faced in its implementation. Using a qualitative approach through in-depth interviews with MSME actors in the creative sector, the data was analyzed thematically to reveal the patterns and dynamics of digital transformation. The results of the study show that most MSMEs have adopted simple technology such as WhatsApp, Google Form, and video tutorials in the process of recruitment, training, and performance recording. However, the limitations of digital literacy of the workforce and infrastructure are the main obstacles. These findings indicate that the digitization of human resources in MSMEs is still gradual and adaptive, and is highly dependent on individual readiness and external support. In conclusion, digital transformation in MSME human resources not only requires technology, but also strengthens human resource capacity and work culture that is inclusive of change. The implications of this study encourage the existence of digital literacy mentoring programs and collaborative policies between business actors, the government, and educational institutions to strengthen the competitiveness of MSMEs in a sustainable manner.